THE CORRELATION BETWEEN STUDENTS’ ENGLISH LEARNING HABITS AND THEIR TOEIC INSTITUTIONAL TEST SCORES IN STATE POLYTECHNIC OF SRIWIJAYA - Zakaria -; Munaja Rahma; Moehamad Ridhwan; Eriza - (Politeknik Negeri Sriwijaya, 2017)
This study was aimed at discovering if the students’ learning habits had a significant correlation as well as gave a significant influence to their TOEIC instituional test scores. One hundred students of State Polytechnic of Sriwijaya, comprising accounting department students, electrical department students and civil engineering students took part as the samples. To estimate the correlation between the variables, a quantitative research method including a Pearson Product-Moment Correlation was used. The result showed that the correlation between students’ learning habits and their TOEIC institutional scores was – ,093 with the significant level of 0.355 which meant no significant correlation and thus, no influence. As for the mean score of the students’ TOEIC test, it reached the number of 329 with the maximum score of 810 and the minimum 165. The students learning habits were found to be on the positive side and showed the indications of their having established good habits in learning English. Some information about TOEIC as well as the ways to getting good scores in TOEIC test were presented. In addition, the qualitative explanations for the results of the research including the implications of the findings were also provided and discussed in this study